PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP STRUKTUR MODAL DINAMIS (PENDEKATAN NILAI PASAR) DI BURSA EFEK INDONESIA - Ruslim, Herman (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
In financing its activity, a firm depends on its capital structure. Although the nature of financing activities through debt and equity is dynamic, underlying motivation for selecting proper capital structure remain a puzzle. This research attempts to study the effect of stock return and the firm’s characteristics on dynamic capital structure. This research used a sample of the 56 companies, which are listed in Indonesia Stock Exchange (BEI) of the period from 1998 to 2007. The analysis method used in this research was time series analysis with generalized method of moment technique (GMM). The research results indicated that firm did not make adjustment to achieve the target capital structure refering to tradeoff theory, based on time series analysis it is concluded that firm characteristic has significant effect on dynamic capital structure such as profitability, retained earning, long term debt and growth opportunity. It was found that the firm characteristic in size and operating risk does not have a significant effect on the dynamic capital structure. Despite of these, the firm characteristics have a significant effect simultaneously on the dynamic capital structure.